Evaluasi Penerapan Sistem Informasi Pemerintah Daerah (SIPD) dalam Pengelolaan Keuangan Daerah di Kabupaten Rote Ndao - Agnes Fontanella Un Bau; Henny A. Manafe; Antonius Y.W.Timunen (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The implementation of the Regional Government Information Sistem (Sistem Informasi Pemerintahan Daerah, SIPD) represents a strategic initiative to strengthen transparency, accountability, and efficiency in regional financial management. Designed to integrate financial data and facilitate standardized reporting across local government units, SIPD is regulated under Minister of Home Affairs Regulation No. 70 of 2019. However, in practice, the adoption of SIPD in various regions, including Rote Ndao Regency, encounters persistent technical and administrative challenges that limit its optimal utilization. This study aims to evaluate the effectiveness of SIPD in managing regional finances within Rote Ndao Regency. Using a qualitative descriptive approach, data were collected through in-depth interviews with key stakeholders, direct observation of system operations, and analysis of relevant documents. The findings reveal that SIPD implementation in Rote Ndao generally complies with the regulatory framework, indicating that the system has been formally adopted and is operational within the expected governance structure. Nonetheless, several issues undermine its effectiveness, including frequent system errors, limited functionality in accounting and reporting modules, and delays in data entry from organizational units. These limitations affect the timeliness, accuracy, and integration of financial reports, ultimately constraining decision-making processes. The study suggests that to fully realize SIPD’s potential, strategic improvements are required. These include enhancing the capacity and skills of human resources responsible for system operation, upgrading IT infrastructure to ensure system stability, and expanding SIPD’s features to meet practical accounting and reporting needs. The research contributes valuable insights for regional governments, policymakers, and system developers, emphasizing the need for continuous system refinement, targeted training programs, and infrastructure investment. By addressing these challenges, SIPD can serve as a more reliable and sustainable tool for promoting transparent and accountable regional financial governance.